2003
DOI: 10.1109/tdei.2003.1176575
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental and low frequency harmonic components of leakage current as a diagnostic tool to study aging of RTV and HTV silicone rubber in salt-fog

Abstract: The paper presents the results of using the fundamental and the low frequency harmonic components of leakage current to study aging of silicone ruhher in saltfog. Experiments have been conducted on RTV and HTV coated rods at different fields (0.25-0.6 kV/cm) and conductivities (1000 to 2500 pS/cm). The onset of dry-hand arcing on samples could he determined hy measuring the low frequency harmonic components. A correlation has been found between the fundamental and low harmonic components of leakage current and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(68 citation statements)
references
References 9 publications
2
58
0
8
Order By: Relevance
“…Therefore, in order to understand the surface degradation of the nano filled silicone rubber insulating material under DC voltages, it is better to carry out the trend analysis of LC signals. El-Hag et al, [20] the condition of insulation structure by the measurement of leakage current adopting moving average measurement technique. They concluded that the moving average measurement technique could provide the tendency of current growth due to aging.…”
Section: Leakage Current Trend Analysismentioning
confidence: 99%
“…Therefore, in order to understand the surface degradation of the nano filled silicone rubber insulating material under DC voltages, it is better to carry out the trend analysis of LC signals. El-Hag et al, [20] the condition of insulation structure by the measurement of leakage current adopting moving average measurement technique. They concluded that the moving average measurement technique could provide the tendency of current growth due to aging.…”
Section: Leakage Current Trend Analysismentioning
confidence: 99%
“…Different ranges of electric fields (0.25-0.6 kV/cm) and conductivity levels (1000-2500 S/cm) have been investigated. The test was conducted for 100 h and both the fundamental and third harmonic components of leakage current was recorded once every 30 s. More details of the experimental setup can be found in [7].…”
Section: Salt-fog Testsmentioning
confidence: 99%
“…Because of this, extensive research has been conducted to measure LC during both accelerated aging tests and in the field. Peak value, number of pulses and low frequency harmonic components of LC have been measured [1][2][3][4][5][6][7]. While it is well known that dry-band arcing is associated with distortion in the LC and hence its low frequency components [7], it is not yet clear when dry-band arcing usually starts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Subba Reddy et al, [7] studied the leakage current behavior on artificially polluted ceramic insulator surface and derived the relation between the surface resistance and leakage current. A.H. El-Hag et al, [8] studied the fundamental and low frequency harmonic components of leakage current to analyses the aging of silicone rubber in salt-fog. They suggested that both the fundamental and low frequency harmonics of leakage current can be used a tools to determine both the beginning of aging and end of life of silicone rubber in salt-fog.…”
Section: Introductionmentioning
confidence: 99%